Evaluation of The Special School Criteria in Meeting the Needs of Students with Mentally Disabled - Ega Kresna Wijaya; Wiryono Raharjo (Journal of Architectural Research and Design Studies, 2023)
The needs of people with cognitive impairment are rarely accommodated in the field of architecture and design. There have been a few standards of design in assessing the suitability of building design for children with the mentally disabled. Evaluation of the design standards for special school inclusion as stipulated in the Education Law No. 33 of 2008 in meeting the needs of mentally disabled students needs to be carried out. This research examined the school design standards for students with mentally disabled based on the relevant literature. The inclusive design proposed in this study can be used to assess the implementation of the inclusive design in meeting the needs of students mentally disabled at special schools. The results of this research add up to the references in the design literature that fit the needs of people with the mentally disabled.Keywords: Design criteria; Inclusive design; Mentally disabled; Special Schools.